(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
The production of groundnut is constrained by several factors, among which is the contamination with Aspergillus sp. In addition to causing quantitative losses, some of the Aspergillus sp. produce highly toxic and carcinogenic chemical substances known as aflatoxins. Aflatoxin contamination of groundnut has gained global significance due to deleterious effects the contaminant has on human and animal health. This study aimed at investigating the occurrence of Aspergillus sp. in different groundnut samples as well as analyzing the samples chemically to detect the presence of aflatoxin in the groundnut samples. Thirty (30) samples of groundnuts were collected from five local markets in Gombe metropolis, namely: Gombe main market, Gombe old market, Riyal, Tashan Dukku, and Arawa market. The kernels were examined for the occurrence of Aspergillus sp. and contamination with aflatoxins. All samples were subjected to microbiological analysis by culturing them on suitable growth medium followed by chemical analysis by Thin-Layer Chromatography (TLC) technique. Twenty-four samples (80%) gave positive readings with TLC technique, and in culture, Aspergillus flavus was isolated from nineteen samples (63%). The concentrations of aflatoxin in these samples were ranged from low to very high, in range of (23.67 – 134.66 μg/Kg kernel).